Relationship Between Generations of Employees to Superior Leadership of SOE - Aryanto Purwadi; Bonar M Sinaga; Anggraini Sukmawati; Alex Denni (Journal of Social Science, 2022)
The competency standards for SOE directors are competency requirements that are prepared so that SOE directors can carry out their roles effectively, taking into account the duties, responsibilities, challenges and targets set. The competency standards are divided into two clusters , namely (1) leading business, and (2) leading people and organization. Leading business competencies consist of six competencies, namely (1) digital leadership, (2) global business savvy, (3) customer focus, (4) building strategic partnerships, (5) strategic orientation, and (6) driving execution. Competence leading people & organization consists of four competencies, namely (1) driving innovation, (2) developing organizational capabilities, (3) leading change, and (4) managing diversity. Bank XYZ employees currently have various generations, namely Gen X, Y, and Z, especially the millennial generation (Gen Y), these various generations form the current corporate culture. Each generation has diverse leadership characteristics and competencies, therefore, the differences in the XYZ generation are important to be studied further. The purpose of this study is to analyze superior leadership competencies according to Generation X, Y, and Z. The method used in this study is to test the correlation or relationship between variables using the SPSS application. The profiles of generations X, Y, and Z each have a relationship on various indicators on each variable from superior leadership, key performance indicators, leading business competencies, and leading people & organization.